Structural plasticity of the ventral stream and aphasia recovery. Issue 1 (July 2017) - McKinnon, Emilie T.; Fridriksson, Julius; Glenn, G. Russell; Jensen, Jens H.; Helpern, Joseph A.; Basilakos, Alexandra; Rorden, Chris; Shih, Andy Y.; Spampinato, M. Vittoria; Bonilha, Leonardo
Abstract : Restrengthening of the residual language network is likely to be crucial for speech recovery in poststroke aphasia. Eight participants with chronic aphasia received intensive speech therapy for 3 weeks, with standardized naming tests and brain magnetic resonance imaging before and after therapy. Kurtosis‐based diffusion tensor tractography was used to measure mean kurtosis (MK) along a segment of the inferior longitudinal fasciculus (ILF). Therapy‐related reduction in the number of semantic but not phonemic errors was associated with strengthening (renormalization) of ILF MK ( r  = −0.90, p  < 0.05 corrected), suggesting that speech recovery is related to structural plasticity of language‐specific components of the residual language network. Ann Neurol 2017;82:147–151